Assessing the effectiveness of GraphoLearn combined with classroom instruction on phonics : a randomised control trial - Bora, Deepti (2023)
Proficiency in reading is a gateway for learning. However, the literacy rate in India stands at only 73% today. Many children studying in English-medium public schools often face a learning disadvantage through the schooling years since they struggle in learning to read in English which manifests into a struggle with reading to learn in later years. This disadvantage is more pronounced in children living in poverty. Thus, consistent efforts towards building foundational literacy skills of these children when developmentally appropriate is important to overcome the learning crisis. The aim of this study was to determine whether GraphoLearn, a computer assisted learning tool, combined with GraphoLearn-aligned classroom instruction can support the foundational English literacy skills of struggling readers in India. Sixty Grade 2 students who were non-native speakers of English and attending an English-medium public school in India participated in the study. Most of the students had at least one year of exposure to English language, however, their literacy skills were not at par with their grade level. In the intervention, all the students were provided 30-35 minutes of classroom instruction on phonics two to three times a week. In addition, the experimental group was also administered GraphoLearn, and the control group played a math game for 20 minutes five to six days a week at school. While exposure to GraphoLearn led to significant improvement in students’ in-game letter-sounds, rime units and word recognition skills, it did not result in transfer to out-of-game measures. However, exposure to the classroom instruction on phonics significantly predicted students’ outside-the-game letter-sound knowledge and phoneme blending skills. These results underline the relevance of instruction on phonics and its efficacy in developing literacy skills in struggling readers.